Llama Llama and the bully goat - Dewdney, Anna (Viking, an imprint of Penguin Group (USA) Inc., 2013)
Here the author takes on the sensitive subject of bullying. With some help from his teacher, Llama Llama finds a way to stand up to Gilroy, a billy goat, and change a bad time to a good time. -- From book jacket.